2008
DOI: 10.4161/cc.7.24.7262
|View full text |Cite
|
Sign up to set email alerts
|

ATRA and KL promote differentiation toward the meiotic program of male germ cells.

Abstract: While it is known that Retinoic Acid (RA) induces meiosis in mouse female fetal gonads, the mechanisms which regulate this process during spermatogenesis are poorly understood. We show that the All trans RA derivative (ATRA) and Kit Ligand (KL) increase meiotic entry of postnatal mouse spermatogonia in vitro without synergism. Competence to enter meiosis is reached by spermatogonia only at the stage in which they undergo Kit-dependent divisions. Besides increasing Kit expression in spermatogonia, ATRA also upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
144
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(154 citation statements)
references
References 43 publications
5
144
0
Order By: Relevance
“…SSCs share molecular markers with undifferentiated spermatogonia (13)(14)(15)(16)(17), and these markers were expressed at significantly higher levels at 1 wk after birth in the testes of WT mice than in cKO mice. However, molecular markers for differentiated spermatogonia (18)(19)(20)(21)(22) were present at significantly higher levels at 1 wk after birth in cKO mice than in WT mice. In addition, germ cells containing the ZBTB16 marker for SSCs and undifferentiated spermatogonia (15) were detected by immunohistochemistry in 2-wk-old WT mice, but rarely in cKO males, and some of their tubules lack proliferating germ cells.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…SSCs share molecular markers with undifferentiated spermatogonia (13)(14)(15)(16)(17), and these markers were expressed at significantly higher levels at 1 wk after birth in the testes of WT mice than in cKO mice. However, molecular markers for differentiated spermatogonia (18)(19)(20)(21)(22) were present at significantly higher levels at 1 wk after birth in cKO mice than in WT mice. In addition, germ cells containing the ZBTB16 marker for SSCs and undifferentiated spermatogonia (15) were detected by immunohistochemistry in 2-wk-old WT mice, but rarely in cKO males, and some of their tubules lack proliferating germ cells.…”
Section: Discussionmentioning
confidence: 94%
“…2A). In addition, sections of testes from 2-wk-old mice were co-immunostained with antibodies to ZBTB16 and to KIT (Table S1), a marker for differentiated spermatogonia (22). There were little apparent differences in the KIT staining in WT, Het, and cKO mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with control testes, we found that transcript levels of several important markers of Sertoli cells, such as Sox9, Sox8, Amh, Fgf9 and Dhh, were significantly downregulated in P0 mutant testes, except for Wt1, which was only slightly reduced. We also examined expression levels of genes for Sertoli cell-derived signalling molecules GDNF (glial cell line-derived neurotrophic factor) and FGF2, involved in SSC self-renewal and proliferation (Meng et al 2000;Simon et al 2007), and KL (Kit ligand) and BMP4, involved in SSC differentiation (Pellegrini et al 2003(Pellegrini et al , 2008. Whereas expression levels of Fgf2 were unchanged, Kl and Bmp4 were downregulated by about 40% and Gdnf by about 70%.…”
Section: Altered Gene Expression In Dicer δ δ δ δ δ/δ δ δ δ δ Testes mentioning
confidence: 99%
“…as Bone Morphogenetic Protein 4, stimulate Kit expression in undifferentiated spermatogonia (Pellegrini et al, 2003;Pellegrini et al, 2008;Zhou et al, 2008). The full-length KIT protein is also expressed in post-natal oocytes, and several reports indicate that it is important for their growth and maturation (Packer et al, 1994;Kissel et al, 2000;Klinger and De Felici, 2002;Hutt et al, 2006).…”
mentioning
confidence: 99%